Anticancer Activities of Extracts and Purified Compounds from Jeruju Putih (Acanthus Ilicifolius L.) - Nurmawati, (2007)
Currently, cancer is Malaysia’s number two killer only preceded by cardiac disease. Unfortunately, there is no effective cure for the disease has yet to be discovered. The diverse local native plants of Malaysia offers an avenue in developing herbal medicines especially for treating chronic diseases such as cancer. Acanthus illicifolius L. is a mangrove plant, which can be commonly found thriving in Malaysian coastal swamps. The plant is commonly (known as Holly-Leaved mangrove and locally) known as jemuju, jeruju or daruju. It has been used traditionally for generations as a treatment for various diseases. The objectives of the study are to separate pure compounds from Jemuju seed and to determine anti-proliferation activity and mechanism pathway of the action pure compounds. Four types of Jemuju seed extracts were separately prepared using distilled water (SA) and organic solvents, which include successively with hexane (FH), ethyl acetate (FE) and methanol (FM). Anti-proliferation activity tests of these extracts were carried out on seven types of cancer cell lines (HeLa, CEM-SS, CaCO-2, HEp-G-2, CaOV-3, MDA-MB-231 and MCF-7). The SA extract was the most active on the HeLa cells (EC50 101 ± 15 μg/ml) while less activity was found on the other test cells. FE extract was most active on CEM-SS cells with an EC50 value of 39.33 ± 4.16 μg/ml followed by HEp-G-2, CaCO-2, CaOV- 3, MCF-7, MDA-MB-231 and HeLa cells, and not activities on MCF-10A cells. On the other hand, no activities were observed for FH and FM extracts. None of the extracs were active on the MCF-10A normal human breast cell line. Results on apoptosis test using DNA ladder and AO/PI methods demonstrated that FE caused internucleosomal DNA damage by causing DNA fragmentation on the cells treated with 40, 60, 80 or 100 μg/ml of this extract compared with non-treated control cells. Using the AO/PI method, a higher percentage of cells which underwent apoptosis were observed in the cells treated with 80 or 100 μg/ml, with EC50 values of 73.91 ± 1.55 and 97.63 ± 1.46%, respectively. On the other hand, only 1.92 ± 0.17% cells underwent apoptosis in non-treated cells. The purification process of FE using liquid chromatography produced 13 fractions where four of the fractions (FE-3, FE-5, FE-6, FE-10) showed high anti-proliferation activity towards MCF-7, MDA-MB-231, HeLa and CaOV-3 cells. Three of the fractions (FE-3, FE-6, FE-10) were further purified using column chromatography, to yeild a total of 67 fractions of which 32 were found to be active against cancer cell lines. The process of re-crystalisation was carried out on the FE-5 fraction until white crystals were produced. Four compounds were successfully purified, their molecular structures have been determined and labeled as J1 (Benzozaxolyne-2-on), N4 (N-benzoxazolol), NW5 (4-hydroxy-3Hbenzoxal- 2-on) dan NW7 (2-hydroxy-2H-1,4-benzoxazin-3(4H)-on). Due to insufficient amount of compounds the molecular structures for the other five compounds could not be obtained. Anti-proliferation activity tests of the pure compounds on five types of cell lines (MCF-7, MDA-MB- 231, HeLa, CaOV-3 and MCF-10A) showed that J1, NW2 and NW3, have no effects. Compounds N3, NW5 and NW7 showed high antiproliferation on activity towards MCF-7, with EC50 values of 7.50 ± 0.32 μg/ml, 8.50 ± 0.21 μg/ml and 7.50 ± 0.65 μg/ml, respectively. NW14 also showed high antiproliferation activity towards MCF-7 and HeLa with EC50 values of 8.00 ± 0.35 μg/ml and 8.21 ± 1.08 μg/ml respectively. Importantly, all of the pure compounds obtained clearly indicated no activities on MCF-10A, which is normal human breast cell line. EC50 values for tamoxifen which was used as positive controls on MCF-7, MDA-MB-231, HeLa and CaOV-3 cells were also obtained. Suppression of oncogene expression by three of the active compounds namely NW5, NW7 dan N4 was also monitored on selected cells. NW5 was found to suppress oncogene expression in MCF-7, MDA-MB-231, HeLa dan CaOV-3. NW7 suppressed oncogene expression in MCF-7 and HeLa cells, while N4 was able to suppress oncogene expression in MCF-7. Thus all compounds tested exhibited suppression of oncogene c-erb-B-2 expression as the mechanism of action on all treated cells. Since the potential of jemuju has been demonstrated, it is hoped that more indepth studies on the plant will continue to be pursued.